The Influence Of Customer Experience On Customer Loyalty Mediated By Emotional Experience Among Shopee Users In The Special Region Of Yogyakarta - Sujoko Sujoko; Syarifah Syarifah; Rakhmat Sigit Widodo (Pt. Anagata Sembagi Education, 2025)
The rapid growth of e-commerce competition requires companies to deliver superior customer experiences to ensure long-term loyalty. In the context of Shopee users in the Special Region of Yogyakarta, customer experience and emotional experience play essential roles in influencing customer loyalty. This study aims to examine the influence of customer experience on customer loyalty, with emotional experience as a mediating variable. A quantitative approach was employed, using purposive sampling. Data were collected through an online questionnaire (Google Form) and analyzed using SEM-PLS. The findings indicate that customer experience has a positive and significant effect on customer loyalty. Additionally, customer experience significantly influences emotional experience, and emotional experience significantly affects customer loyalty. Furthermore, emotional experience is proven to mediate the relationship between customer experience and customer loyalty. These results highlight the importance of emotional engagement in strengthening customer loyalty in e-commerce platforms. Therefore, Shopee and similar platforms must enhance emotional touchpoints by providing responsive, personalized services that foster feelings of satisfaction, appreciation, and comfort. This study is limited to Yogyakarta and online survey distribution. Future research should expand the geographical scope and consider mixed-method approaches.